2019
DOI: 10.1055/s-0039-1698374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Morus nigra L. in Bone Healing

Abstract: Morus nigra L., popularly known as blackberry, mulberry or blackberry bush, is a plant species widely used by folk medicine. Although there are few scientific studies that denote its therapeutic features, an important highlight of black mulberry is the recurrent use of tea leaves in popular environment for treatment of climacteric because it is considered a source of substances with estrogenic activity, which, if deficient, decreases osteoblastic action. Thus, the objective of the present study was to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Diverse bioactive compounds have been isolated from the mulberry fruit depending on the stage of maturity and are responsible for its miscellaneous biological activities. These plants can be used as phytoestrogens for hormone replacement therapy and used for the management of climacteric and osteoporosis in elderly females (Cohen, 2005; Costa et al, 2019). One of the animal study concluded that encapsulated mulberry fruit extract can be used to reduce inflammation, oxidative stress, and metabolic parameters associated with the metabolic syndrome of menopause (Wattanathorn et al, 2019).…”
Section: Management Of Menopause and Related Disordersmentioning
confidence: 99%
“…Diverse bioactive compounds have been isolated from the mulberry fruit depending on the stage of maturity and are responsible for its miscellaneous biological activities. These plants can be used as phytoestrogens for hormone replacement therapy and used for the management of climacteric and osteoporosis in elderly females (Cohen, 2005; Costa et al, 2019). One of the animal study concluded that encapsulated mulberry fruit extract can be used to reduce inflammation, oxidative stress, and metabolic parameters associated with the metabolic syndrome of menopause (Wattanathorn et al, 2019).…”
Section: Management Of Menopause and Related Disordersmentioning
confidence: 99%